Pengujian produk minuman herbal berbasis teh (Camellia sinensis L. Kuntze.), bunga telang (Clitoria ternatea L.) dan daun mengkudu (Morinda citrifolia L.): toksisitas , sifat antidiabetik dan penerimaan konsumen - Tarsisius Dwi Wibawa Budianta; Paini Sri Widyawati; Sentot Joko Raharjo (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
The production of herbal drinks by combining three ingredients, namely tea leaves, butterfly pea flowers, and noni leaves, is intended to obtain herbal drinks that have health benefits and can be accepted by consumers. The reason for using the three ingredients is because tea leaves have high antioxidant, noni leaves have antioxidant and antimicrobial properties, and butterfly pea flowers have high antioxidant, and also become an attractive natural coloring for drinks. The experiment was carried out by mixing the three ingredients with varying weight ratios, as many as 9 treatments with a weight of 2.25 g each and put into a tea bag, which was then steeped using hot water with a volume of 200 ml at 90 ± 1 oC, for 3 minutes. Identification was carried out by toxicity tests on shrimp larvae, alpha-glucosidase enzyme inhibition tests, consumer acceptance levels through aroma-taste and colour preference tests, and searching for antioxidant compound profiles using GC-MS and FTIR. The experiment was carried out by combining the three ingredients with varying weight ratios, as many as 9 treatment with a weight 0f 2.25 g each and put into a tea bag, which was then steeped using hot water with a volume of 200 ml at 90 ±1oC, for 3 minutes. From the experiment, it was obtained that herbal drinks were proven to have bioactive compounds with LC50 values between 98.94-351.59, capable of inhibiting the performance of alpha glucosidase enzymes with an inhibition level of between 13.60 -63.97%; the level of panelist acceptance using a preference test with a rating scale of 1 to nine obtained a value of 3.34 (slightly dislike) -6.2 (slightly like) for aroma-taste, while for the color preference test obtained a value of 3.9 (slightly dislike) -6.22 (slightly like). From the GC-MS test, the compounds esani and 1,3,7-Trimethyl-3,7-Dihydro-1H-purine-2,6-dione were identified, and from the FTIR test, the compounds chlorophyll, pheophytin, aromatic compounds, polyphenols, catechins, and other compounds were identified.